The gravitational afterglow of boson stars. (16th March 2023) - Croft, Robin; Helfer, Thomas; Ge, Bo-Xuan; Radia, Miren; Evstafyeva, Tamara; Lim, Eugene A; Sperhake, Ulrich; Clough, Katy
Abstract: In this work we study the long-lived post-merger gravitational wave signature of a boson-star binary coalescence. We use full numerical relativity to simulate the post-merger and track the gravitational afterglow over an extended period of time. We implement recent innovations for the binary initial data, which significantly reduce spurious initial excitations of the scalar field profiles, as well as a measure for the angular momentum that allows us to track the total momentum of the spatial volume, including the curvature contribution. Crucially, we find the afterglow to last much longer than the spin-down timescale. This prolonged gravitational wave afterglow provides a characteristic signal that may distinguish it from other astrophysical sources.